The Politics of Booklists - Tjamke Snijders (BMGN: Low Countries Historical Review)
High medieval booklists are routinely interpreted as administrative sources that existed to inventory book collections, somewhat similar to present-day library catalogues. Historians, however, have found them curiously unreliable and impractical. A case study of the Benedictine monastery of St. Laurent in Liège suggests a different approach to booklists. The thirteenth-century St. Laurent booklist was used, I argue in this article, to position the library as a centre of trinitarian expertise, fundamentally orthodox, and highly respectable. In order to do so, the booklist had to strategically neglect several books that might detract from the image of a perfect library. Booklists such as those from St. Laurent were, therefore, complex mixtures of the administrative with the political, and should be studied as such.